Studi Perilaku Wajib Pajak Usaha Mikro Kecil Menengah di Kabupaten Gorontalo Utara - Afriana Lomagio (Al-Buhuts, 2019)
This research was conducted to analyze the behavior of UMKM Taxpayers in North Gorontalo District. The results of this study are expected to provide input and develop research in the field of accounting, especially in the field of taxation and behavioral accounting. This research uses descriptive qualitative method. There are four informants who were selected based on the criteria of the researcher. Meanwhile, the data collection is completed by using the unstructured interview method. The results showed that the willingness of informants to register as taxpayers was driven by regulatory demands. In other side, the implementation of the Self Assessment System has not been fully implemented by the UMKM Taxpayer. This is not only by the lack of knowledge of taxpayers, as well as the condition of taxpayers living in North Gorontalo Regency which is The central of Tax office is quite far from Gorontalo City, it makes taxpayers take another account material that must be sacrificed rather than those issued to fulfill tax obligations.